CREDIT FACILITIES IN AGRICULTURE WITH SPECIAL EMPHASIS ON LIVESTOCK - OGUNLAYI, JIDE (Nigerian Journal of Animal Science, 2023)
I feel highly honored and appreciative of the invitation by the Executives of Animal Science Association of Nigeria (ASAN) and the Local Organizing Committee (LOC) to its 4'" Annual Conference to present this paper. I also wish to congratulate all members and friends of ASAN for the appropriateness of this paper to the theme of our association's 4"' Annual Conference "Sustainability of the Nigerian Livestock Industry in the Twenty-First Century". It is my hope that we shall use this unique opportunity to eventually restore the much-desired progressive partnership between livestock industry and banking industry in Nigeria. Please grant me the indulgence of looking at the, importance of livestock agriculture to the Nigerian economy before talking about the situation of credit facilities for its development. It is an established fact that insufficiency of livestock products is a major contributory factor to the growing gap between food demand and food supply in Nigeria. liege (1998) in her assessment of the livestock development process documented agriculture to have contributed 56% of the Cross Domestic Product (CDl) in the 1960 - 69 period, just average of 24 O/O in the 10 year period immediately after and fluctuated between 21 and 23 % in the 1981 - 85 period. Nauru (1998) reported livestock to have contributed about 5 O/O of Agricultural GDP and it is second to none in the nutritional value of its various products. Besides being the major source of protein for the Nigerian population, its sub-sector could readily provide employment opportunities, raw materials for local industries and could be a high foreign exchange earner. Many problems have impeded growth and development of the livestock industry and militated against a smooth and progressive move towards self-sufficiency in animal production and supply (Lunge, 1998). . - Mr. Chairman, members of the High Table, Ladies and Gentlemen, the importance of credit facilities to any business venture including agricultures; TN not be over emphasized. It will be important at the introductory state of this presentation to recognize that funding of livestock projects is a combination of equity (self) financing and borrowed funding/grant. I want to therefore mention it that it is not out of place for any business promoter to ask for complementary funding from credit institutions. Such financial support is both for acquisition of assets like farm houses, stocking of farm animals, feeding and drinking apparatus, feed hammer mill, feed mixer, preservation and storage devices, transportation vehicles, electricity generators, information technology and communication devices and also for day-to-day running of the business.